PENERAPAN METODE FEM (FUN AND EASY MATH) UNTUK MENINGKATKAN KEMAMPUAN SISWA SD ISLAM AL-FALAH DALAM MENYELESAIKAN MASALAH TENTANG MATERI LUAS DAN KELILING BANGUN DATAR - Liska Novi Yanti Pane (Jurnal Didaktika Pendidikan Dasar, 2019)
The aim of this research is to describe the improvement of students’ problem-solving skills on the Periphery and Area of Flat Shapes through the implementation of FEM method. The method of this research is a classroom action research (CAR) that consists of 2 cycles according to Kemmis & Mc. Taggart Model of CAR. The subjects of this research are 17 students of SD Islam Al-Farah that consists of 5 males and 12 females. The result of the research shows the improvement of students’ ability in mathematical problem-solving. The results of the cycle I of the research are obtained from the students who completed minimum criteria that less than 36%. Meanwhile, the results of cycle II have increased with 94% at the first treatment, 88.23% at the second treatment, and finally 94,11% at the third treatment. Based on the results of this research, the implementation of FEM method through multiplication box and unit lift can improve students’ ability in mathematical problem-solving.